Development of express method for calculation of internal irradiation doses of laboratory rats using the chamber models - A. I. Lypska; I. P. Drozd (Ядерна фізика та енергетика)
On the basis of theoretical and experimental material, the calculation method of doses of internal irradiation of laboratory rats using the multichamber dosimetry model of metabolism of strontium. The developed express method allows to simplify substantially the process of calculation of absorbed doses of internal irradiation after the chronic intake of 90Sr + 90Y in the organism of laboratory rats.